(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2014)
Information and communication technologies are changing the world, they have also revolutionized education. Social networks for educational purposes are a challenge for teachers regarding new curriculum guidelines which require different learning scenarios. The present research demonstrates a collaborative learning experience among teachers and students from Agribusiness Engineering undergraduate program, taking Introduction to Computing and ICT Elective and Technology Management subject at UCLA. We endorse that the research was based on the use and potential social networks allow us today, especially the second most used worldwide network known as Facebook. It was also used to create a group to organize working committees of the First Conference on ICT and Management technology. With a simulation technique of participant observation, monitoring and a survey in order to measure the level of satisfaction, the results reflect the acceptance of experience, and the way they should be used properly to maximize resources. That requires training and lifelong learning.